2005
DOI: 10.1159/000087048
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and Alcohol Habits as Risk Factors for Benign Digestive Diseases in a Japanese Population: The Radiation Effects Research Foundation Adult Health Study

Abstract: Background: Although an association between benign digestive diseases and smoking or drinking habits was reported, consistent results have not been obtained either in European, American or Japanese populations. Methods: Smoking and alcohol habits as risk factors for the incidence of gastric ulcer, duodenal ulcer, chronic liver disease and cirrhosis as well as cholelithiasis were examined using the longitudinal data of the Adult Health Study collected biennially between 1958 and 1998. During 1958–1998, 1,093 ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…Smoking is a well-known contributor to GI ulcer disease [19][20][21]. The risk of GI ulcer is believed to be related to the quantity of smoking [22].…”
Section: Discussionmentioning
confidence: 99%
“…Smoking is a well-known contributor to GI ulcer disease [19][20][21]. The risk of GI ulcer is believed to be related to the quantity of smoking [22].…”
Section: Discussionmentioning
confidence: 99%
“…Those experiencing a perceived higher work stress may smoke and drink more than others and may engage in less physical activity. All of these factors may lead to the susceptibility of these individuals to peptic ulcers [Räihä et al, 1998;Shigemi et al, 1999;Andersen et al, 2000;Cheng et al, 2000;Rosenstock et al, 2003;Franke et al, 2005;Yamada et al, 2005]. In addition, some stressors relating to the physical environment of work place, ergonomics, and organizational structure in the workplace [Wong et al, 2002] have been shown to affect gastrointestinal illnesses directly.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously thought that an association existed between alcohol consumption and benign digestive disorders, such as peptic ulcer. However, it is now thought that diet does not have a significant role, as duodenal ulcers are primarily due to a Helicobacter Pylori infection, or intake of non-steroidal inflammatory drugs (Cummings 2000;Yamada et al 2005). However, alcohol can be a 'problem food' for anyone with an ulcer, or at risk of an ulcer, and should be avoided or consumed sparingly.…”
Section: Alcohol and Peptic Ulcersmentioning
confidence: 99%